ANALYSIS OF LAND COVER (LULC) DYNAMICS OF A SPECIFIC AREA BASED ON GIS AND REMOTE SENSING TECHNOLOGIES - Azamjon Jobborov,; Azamat Khoshimov, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Land  use  and  land  cover  (LULC)  changes  represent  a  critical challenge for sustainable environmental management, urban planning, and ecosystem conservation  under  conditions  of  rapid  population  growth  and  socio-economic transformation.  This  article  provides  a  comprehensive  analysis  of  LULC  dynamics within a specific geographic area based on the integration of Geographic Information Systems (GIS) and remote sensing technologies. The study synthesizes recent scientific literature  to  examine  methodological  approaches,  data  sources,  and  analytical techniques used for detecting and monitoring spatial and temporal land cover changes. Particular emphasis is placed on the application of multi-temporal satellite imagery, high-resolution data, and advanced classification methods, including machine learning algorithms, to improve accuracy and interpretability of LULC assessments. The review also highlights the influence of socio-economic drivers, policy decisions, and climatic factors  on  land use transformations, emphasizing the need  for interdisciplinary and localized case studies. The findings demonstrate that GIS and remote sensing provide robust and efficient tools for understanding complex land cover dynamics and support evidence-based  decision-making  for  sustainable  land  management.  The  article concludes by identifying existing research gaps and proposing directions for future studies that integrate technological innovation with socio-environmental perspectives.